Β-thalassemia minor, carbohydrate malabsorption and histamine intolerance. Issue 4 (2nd October 2017) - Schnedl, Wolfgang J.; Schenk, Michael; Lackner, Sonja; Holasek, Sandra J.; Mangge, Harald
ABSTRACT: Background : β-thalassemia minor is characterized by reduced β-haemoglobin chain synthesis and sometimes mild anaemia, although carriers of β-thalassemia minorare usually clinically asymptomatic.Nonspecific abdominal complaints may be caused by gastrointestinal carbohydrate malabsorption (lactose and fructose) and/or malabsorption of biogenic amines (histamine), or proteins (gluten). Objectives : We report on two patients with β-thalassemia minor suffering nonspecific abdominal symptoms due to a carbohydrate and histamine malabsorption. Design/methods : The diagnosis of β-thalassemia minorwas done with peripheral blood smear and cellulose acetate electrophoresis. Carbohydrate malabsorption was diagnosed with hydrogen breath tests and, histamine intolerance (HIT) with a serum diamine oxidase value <10 U/ml and more than two gastrointestinal symptoms described for HIT. Conclusion : The symptoms of gastrointestinal malabsorption in these two patients with β-thalassemia minor were treated successfully with an individually-tailored diet free of symptom causing carbohydrates and histamine.